ANALYSIS OF REGIONAL TAX REVENUE AND BUMD CONTRIBUTION TO GENUINE REGIONAL REVENUE (PAD) JENEPONTO REGENCY - Masrullah, Masrullah (Jurnal Ekonomi Balance, 2018)
This study aims to find out (a) How much influence the Regional Tax revenue has on PAD (b) How big is the contribution of BUMD to (c) What is the growth rate of local tax revenues and the contribution of BUMD in Jeneponto Regency for the period 2014-2018. The type of research used is case study research with a quantitative descriptive approach. The processed data is a summary of the Realization of the APBD Description. Jeneponto Regency from 2014 to 2018 obtained from the annual report. The results of data analysis show that (1) Regional Tax Contributions to the Original Regional Income of Jeneponto Regency amounted to 18.96% in 2014; 14.62% in 2015; 13.10% in 2016 and began to rise in 2017 to 13.50%; and in 2018 it rose again by 3.89%; to be 17.39%; (2) the contribution of BUMD to the Jeneponto Regency Original Revenue, amounting to 9.14% in 2014; 7.99% in 2015; 7.01% in 2016; 5.86% in 2017 and up to 8.47% in 2018, (3) the growth rate of the contribution of Regional Taxes to Regional Original Revenues tends to decrease from 2014 to 2016, and increases in 2017 to 2018. Levels the growth of BUMD profit contribution to Regional Original Income tends to decrease from 2014 to 2017, and increase in 2018.